1982
DOI: 10.1002/jobm.19820220507
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the mycelial growth pattern on the individually regulated cell cycle in Streptomyces granaticolor

Abstract: The growth behaviour of Streptomyces granaticolor E T H 7437 was studied by the microculture technique. The kinetics of growth and branching were recorded and, since elongation was found t o be restricted to apical elongation sites (e-sites), the rate of elongation per site (a) was determined as well. The mycelia grew exponentially. Initially the growth was dependent on a of the germ tube, but after the start of branching, growth paralleled the exponential increase of the number of branches while a attained a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Following germination, hyphal extension occurred at a rate of ϳ20 m h Ϫ1 and FtsZ-EGFP rings were laid down ϳ56 m behind the growing tip. Streptomyces granaticolor lays down septa 28 m from the hyphal tip (17), and as septum formation is dependent on the initial formation of a ring of FtsZ (26), it appears that either there is some variability in the frequency of septum formation between these two species or cultivation conditions affect septal frequency. It was thought that the subapical daughter compartment created a new extension site through branching (14) and this new apical cell was eventually partitioned from the subapical cell by a new septum.…”
Section: Discussionmentioning
confidence: 99%
“…Following germination, hyphal extension occurred at a rate of ϳ20 m h Ϫ1 and FtsZ-EGFP rings were laid down ϳ56 m behind the growing tip. Streptomyces granaticolor lays down septa 28 m from the hyphal tip (17), and as septum formation is dependent on the initial formation of a ring of FtsZ (26), it appears that either there is some variability in the frequency of septum formation between these two species or cultivation conditions affect septal frequency. It was thought that the subapical daughter compartment created a new extension site through branching (14) and this new apical cell was eventually partitioned from the subapical cell by a new septum.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, during vegetative growth cell division results in the formation of hyphal cross‐walls, which are widely spaced, and delimit adjacent elongated compartments that each contain multiple copies of the genome. Studies of Streptomyces granaticolor suggested initiation of division at the middle of the growing apical cell when it reaches a certain length (Kretschmer, 1982). However, considerable variation is seen in the frequency and spacing of vegetative septa in Streptomyces hyphae, both between different species and within a single species between different growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We find in this study that, although very slow, the growth kinetics of Frankia sp. strain CcI3 resembled that of other filamentous actinomycetes in having an exponential increase in total mycelium length and arithmetic or pseudolinear increase in individual hyphae (Kretschmer 1978(Kretschmer , 1982Allan and Prosser 1983). Moreover, the interbranch distances of strain CcI3 were similar to those described in Streptomyces coelicolor A3(2) (Allan and Prosser 1983).…”
Section: Discussionmentioning
confidence: 53%